Upaya Meningkatkan Hasil Belajar IPA Melalui Metode Pembelajaran Interaktif - Sari, Anggy Permata (Yayasan Sembilan Pemuda Indonesia, 2024)
The low learning outcomes of the science subject matter were caused by teachers. After the teacher felt a decrease in students’ interest in science learning. It can be observed that there is still material that seems difficult for children to understand: one of which is related to